Visual Political Communication in Popular Chinese Television Series - Schneider, Florian; Dudbridge, Glen; Pieke, Frank N. (BRILL, 2012)
In Visual Political Communication in Popular Chinese Television Series, Florian Schneider analyses political discourses in Chinese TV dramas, the most popular entertainment format in China today.
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Europe (lieu de production du savoir); Chine (corpus analysé); Pays-Bas (lieu de production du savoir); Royaume-Uni (lieu de production du savoir); _Nettoyé